Increasing the interval between repeated anesthetic exposures reduces long‐lasting synaptic changes in late post‐natal mice. Issue 1 (18th July 2020) - Ju, Xianshu; Cui, Jianchen; Lee, Yulim; Park, Sangil; Hong, Boohwi; Yoo, Sungho; Kim, Yoon Hee; Ko, Youngkwon; Lim, Chaeseong; Lee, Sun Yeul; Kweon, Gi Ryang; Heo, Jun Young; et al.
Abstract : Abstract: While recent studies strongly suggest that a single, short anesthetic exposure does not affect neurodevelopment, the effects of multiple exposures remain unclear. Unfortunately, studying "multiple exposures" is challenging as it is an extremely heterogeneous descriptor comprising diverse factors. One potentially important, but unrecognized factor is the interval between anesthetic exposures. In order to evaluate the significance of interval, we exposed post‐natal day 16, 17 mice to three sevoflurane exposures (2.5%, 1 hr) with short (2 hr) or long (24 hr) intervals. Changes in synaptic transmission, plasticity, protein expression, and behavior were assessed in male and female mice. We discovered that short‐interval exposures induced a female‐dependent decrease in miniature inhibitory post‐synaptic current (mIPSC) frequency 5 days after the last exposure (control: 18.44 ± 2.86 Hz, sevoflurane:14.65 ± 4.54 Hz). Short‐interval sevoflurane exposed mice also displayed long‐term behavioral deficits at adult age (hypoactivity, anxiety). These behavioral changes were consistent with the sex‐dependent changes in inhibitory transmission, as they were more robust in female mice. Although there was no change in learning and memory, short‐interval sevoflurane exposures also impaired LTP in a non‐sex‐dependent manner (control: 171.10 ± 26.90%, sevoflurane: 149.80 ± 26.48 %). Most importantly, we were unable to find long‐lasting consequences in mice that received long‐interval sevoflurane exposures. Our study provides novel insights regarding the significance of the interval between multiple exposures, and also suggests that the neurotoxic effects of multiple anesthetic exposures may be reduced by simply increasing the interval between each exposure. Abstract : Multiple anesthetic exposures during neurodevelopment may cause long‐term negative consequences. By exposing late post‐natal mice to the same cumulative dose of anesthesia but only at different intervals (short vs. long), we identified that a single factor, the interval between exposures, can significantly affect the level of neurotoxicity. Our results therefore suggest that the neurotoxic effects can be reduced by simply increasing the interval between each exposure. Left: Short‐interval anesthetic exposures induce changes in synaptic transmission, plasticity, and behavior. Right: Long‐interval anesthetic exposures do not induce long‐lasting changes.